Bronchial reactivity to methacholine after combined heart-lung transplantation. Issue 12 (December 1988) - Banner, N R; Heaton, R; Hollingshead, L; Guz, A; Yacoub, M H
Abstract : The operation of combined heart-lung transplantation results in acute denervation of the heart, lungs, and airways below the level of the trachea. The bronchoconstrictor response to inhaled methacholine of 12 recipients of heart-lung transplants was compared with that of 12 recipients of heart transplants having similar medication and 12 normal subjects. The median dose of methacholine that produced a reduction of at least 20% in the FEV1 (PC20) for the recipients of heart-lung transplants (8 mg/ml) was significantly lower than that for the recipients of heart transplants (64 mg/ml) and normal subjects (greater than 64 mg/ml). The increased airway reactivity may be related to the effects of chronic pulmonary denervation or subclinical inflammation in the airways. The effect of denervation on the response to full inspiration during bronchoconstriction was studied in six patients with heart-lung transplants by means of partial and maximal forced expiratory manoeuvres. Four showed bronchodilation after a deep breath, indicating that this response can occur after extrinsic pulmonary denervation in man. The patients with heart-lung transplants described a "tight" sensation in the anterior chest during bronchoconstriction, indicating that this sensation is not dependent on pulmonary innervation.